Phenotypic and genetic diversity of the Anjian chicken in China - Yang, Na; Tang, Chi; Azimu, Wumaierjiang; Wang, Hui’e; Tuersuntuoheti, Tuerdibake; Yalimaimaiti, Yinamujiang; Kelimu, Nuermanu; Li, Hang Sen; Wumaier, Alfera; Sun, Xiao Yuan; Hao, Chao Shuai; Muhatai, Gemingguli (Frontiers in Ecology and Evolution, 2022)
The Anjian chicken is a local breed in Hotan, Xinjiang, China. Herein, we studied the morphological characteristics and genetic diversity of the Anjian chicken population. The findings of this study could inform the genetic improvement strategy of this breed. Phenotypic characteristics investigated included the diversity in the general appearance, feather color, and crowing length of the Anjian cocks. The population structure of the Anjian chicken and its relationship with other chicken breeds were also assessed based on mitochondrial DNA (mtDNA) D-loop sequence analysis. Phenotypically, the feather color of the Anjian chicken varied considerably. The sequence diversity analysis revealed the following: nucleotide diversity (Pi) was 0.00618, haplotype diversity (Hd) was 0.776, the average number of nucleotide differences (k) was 7.631, and Tajima′s (D) was -0.00407, indicating that Anjian chicken is moderately genetically diverse. Further phylogenetic analysis revealed that the Anjian chicken breed has 10 haplotypes clustered into two branches. Genetic distance and median network analysis showed that the mtDNA D-loop sequence of the Anjian chicken was distributed in many different clusters of the tree. These data demonstrate that even though the Anjian chicken mainly originated from red jungle fowl, it has multiple maternal origins. In conclusion, the Anjian chicken is highly genetically diverse.